Ubrogepant for the treatment of migraine. (2nd May 2020) - Curto, Martina; Capi, Matilde; Cipolla, Fabiola; Cisale, Giusy Ylenia; Martelletti, Paolo; Lionetto, Luana
ABSTRACT: Introduction: Migraine is a neurovascular disorder involving neurogenic inflammation and transmission of trigeminovascular nociceptive pathways mediated by Calcitonin Gene-Related Peptide (CGRP). Several small molecules antagonizing the CGRP receptor have been developed as migraine-specific acute medications. The CGRP receptor antagonist ubrogepant, also known as MK-1602, has been recently evaluated in phase III clinical trials for clinical efficacy and long-term safety as an abortive migraine treatment. Areas covered: This paper discusses the pharmacodynamics, pharmacokinetics, clinical efficacy, safety, and tolerability profile of ubrogepant for the acute treatment of migraine with or without aura. Expert opinion: Ubrogepant, a selective CGRP antagonist belonging to the gepants family, has been evaluated in large short- and long-term Phases 2 and 3 clinical trials aimed to assess clinical efficacy and safety as acute migraine medication. It did not significantly affect liver function and was not associated with other serious adverse events. Long-term non-serious adverse events were similar between placebo and ubrogepant. The efficacy was evaluated in large placebo-controlled studies and ubrogepant 50 mg and 100 mg was superior, even if the therapeutic gain seems to be low. Nevertheless, the favorable safety profile compared to other abortive drugs makes ubrogepant a promising option for the acute treatment of migraine.